Histopathological Analysis of the Respiratory Tract. Issue 4 (11th December 2014) - Scudamore, Cheryl L.; McInnes, Elizabeth F.
Abstract : The basic anatomy of the mouse respiratory system is similar to that of other mammals and can be usefully examined under the light microscope in phenotyping studies, inhalation toxicity studies, and studies involving mouse models of human disease. In many studies, however, only the lungs are examined, leaving the possibility that phenotypic information from the majority of the conducting airways is lost. This unit provides standard approaches for tissue collection at necropsy and subsequent selection of a range of respiratory tissues for histological and pathological analysis. The major anatomical features to be found in each section are highlighted, and potential artifacts and methods to avoid them are discussed. © 2014 by John Wiley & Sons, Inc.